The Involvement of Lactosylceramide in Central Nervous System Inflammation Related to Neurodegenerative Disease - Yu, Wen; Ying, Jun; Wang, Xifeng; Liu, Xing; Zhao, Tiancheng; Yoon, Sungtae; Zheng, Qingcui; Fang, Yang; Yang, Danying; Hua, Fuzhou (Frontiers in Aging Neuroscience, 2021)
Neurodegenerative diseases are a class of slow-progressing diseases based on neurodegenerative lesions, with the accelerating process of aging, the burden on families and society will be more highlighted. These mainly include Multiple sclerosis（MS）,Alzheimer’s disease (AD), Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS) and so on. In recent years, studies have shown that Lactosylceramide(LacCer) plays a crucial role in the progression of these neurodegeneration although these diseases have different mechanisms and characteristics. Based on the latest research progress, this paper expounds LacCer's pathogenic mechanism in driving central inflammation, membrane microstructure domain and metabolite neurothionin lipids（Lipid rafts）, and discusses in detail the link with the pathogenesis of neurodegenerative diseases, with a view to providing new strategies and ideas for the study of pathological mechanisms research and drug development of neurodegenerative diseases in the future.